Teacher's Written Feedback in Academic Writing Class: Students' Perceptions - Aprilia, Christina; Listyani, Listyani; Palupi, Victoria Usadya (Universitas Muria Kudus, 2023)
Teacher's written feedback is one crucial thing that influences students' success in writing class. This feedback can benefit students' essays and writing performances in writing class. This study focuses on Academic Writing students' perceptions of teacher's written feedback in Academic Writing class. The purpose of this study is to investigate Academic Writing students' perceptions toward teacher's written feedback for their writing performances in Academic Writing class. This study was conducted in the English Language Education Program (ELEP), the Faculty of Language and Arts, Universitas Kristen Satya Wacana. The participants for this study were 31 students who were taking an Academic Writing course in Semester Gasal, 2022/2023 academic year. This study used questionnaires and semi-structured interviews to gather the data. The result showed that Academic Writing students had varied perceptions of teacher's written feedback from their lecturers. There were three types of students' perceptions of teacher's written feedback which were positive, mixed, and negative. This study hopefully can contribute valuable suggestions for the Academic Writing teacher in giving good written feedback and reveals the fact that teacher's written feedback can enhance students' writing performance.